Milk al-Yamin dalam Perspektif Ulama Tafsir Kontemporer - Nurkumala, Indah Ayu; Mubarok, Nafi’ (Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2024)
Abstract: Efforts to interpret the term milk al-yamin have been widely undertaken throughout various periods of Qur’anic exegesis. In the contemporary era in particular, numerous interpretations of this phrase have emerged. One notably controversial view in the field of tafsir suggests a shift in meaning from “slave” to “a sexual partner outside of conventional marriage,” who is nonetheless lawful to engage with. Using a qualitative approach and a descriptive-analytical method, this study seeks to uncover how contemporary exegetes interpret milk al-yamin. The findings show that contemporary scholars generally define milk al-yamin as female slaves obtained through victory in battle against enemies in defense of the faith. The absence of a context of slavery in the modern era does not necessarily lead to a change in meaning or render the concept irrelevant. On the contrary, the interpretations offered by contemporary exegetes reflect the Qur’an’s spirit of humanizing individuals—even in a time that claims the abolition of slavery, while in reality various forms of modern slavery still persist.